HOW BANKING STOCK PRICES RESPOND TO GROSS DOMESTIC PRODUCT, EXCHANGE RATES AND INFLATION: EMPIRICAL STUDIES OF INDONESIA AND HONG KONG - Idah Zuhroh (Jurnal Reviu Akuntansi dan Keuangan, 2020)
The study aims to analyze how banking stock prices response to GDP, inflation and exchange rate in the Indonesia Stock Exchange (IDX) and Hong Kong Stock Exchange (HKEX). For this purpose a panel data of of seven listed bank’s company in each country for the 2016Q1-2018Q4 period is used for empirical analysis.  The model analysis using static and dynamic panel regression.  Static regression used are Fixed Effect, Random Effect or Common Effect by Chow test while dynamic regression used Generalized Method of Moments (GMM). The results revealed that stock prices respond positively to GDP and negatively to exchange rates on both exchanges. Furthermore, inflation was responded positively by stock prices on IDX, meanwhile inflation was responded negatively at HKEX. The differences in the values of the regression coefficients on two exchanges represented that the IDX is less responsive to the exchange rate and inflation variables than HKEX. Contrary, GDP was found more sensitive in Indonesian compared to Hongkong.  Dynamic regression is proved that HKEX is more efficient than IDX. Investors in IDX are still responding to the prices of the previous period, while investors at HKEX responded immediately to macroeconomic variable information without considering stock prices in the previous period.